ANALYSIS OF STUDENTS LEVEL OF MATHEMATICAL CREATIVE THINKING ABILITY IN TERMS OF LEARNING STYLE - Siregar, Khofifa Romaito; Saragih, Sisca Sri Dewi; Priani, Nurul Kholiza (Algebra : Jurnal Pendidikan, Sosial dan Sains, 2025)
The ability to think creatively is an ability that requires a process with the aim that students can solve problems variedly and correctly. Understanding and obtaining information on a problem is a process experienced by students in order to solve mathematical problems, which is called learning style. The purpose of this study is to analyze and describe students' creative thinking skills in terms of learning styles. The type of research used in this study is qualitative research. In the process of collecting data, this research uses two methods, namely tests and interviews. From the results of this study, it was concluded that 35 students had Visual learning styles, 9 who had auditorial learning styles, 7 who had kinesthetic learning styles, 2 who had kinesthetic visual learning styles, and 1 student with auditorial visual learning styles. However, this study only selected 3 students with visual learning styles. The level of creative thinking ability in conscientious students is classified at the level of creative thinking less creative, moderately creative, and creative).